Evaluation of Tartrazine Solution as a Potential Gamma Dosimeter Material - Arumbifa, Farhansyah Yunandani; Kurniawan, Deni; Diani, Desalsa Anggoro; Praja, Dika Bhakti; Ajri, Fauziah Ulfah; Dewi, Ariyani Kusuma; Ariyanti, Dhita (International Journal of Applied Sciences and Smart Technologies, 2024)
Radiation dosimetry plays a crucial role in various fields, including medical, industrial, and environmental applications. Accurate and reliable dosimeters are essential for measuring and controlling radiation exposure. This study aims to evaluate the stability of the food dye tartrazine as a potential gamma radiation dosimeter. The need for accessible and cost-effective dosimetric materials motivates the exploration of tartrazine's capabilities in this regard. This research investigates the response of tartrazine solutions under varying gamma radiation doses (0 to 3.118 kGy) using UV-Vis spectrophotometry to measure absorbance at a wavelength of 424 nm. The results demonstrate a significant decrease in absorbance with increasing radiation doses, indicating decolorization due to oxidative reactions triggered by hydroxyl radicals (OH·) generated during irradiation. Tartrazine, which imparts a yellow color through its diazenedyl (-N=N-) bonds, undergoes bond cleavage upon gamma radiation exposure, resulting in a permanent color change. Further analysis reveals that tartrazine-based dosimeters exhibit optimal stability for less than four weeks. Therefore, tartrazine solution can serve as an effective gamma radiation dosimeter for short-term applications. This study provides a foundation for developing new dosimetric materials, emphasizing the importance of ongoing research to enhance radiation safety and measurement accuracy.Keywords: Dosimeter, Gamma Irradiation, Radiation, Stability, Tartrazine.